2018
DOI: 10.3389/fpsyg.2017.02333
|View full text |Cite
|
Sign up to set email alerts
|

EMDR as Add-On Treatment for Psychiatric and Traumatic Symptoms in Patients with Substance Use Disorder

Abstract: Background: Substance use disorders (SUD) are patterns of substance use leading to severe impairment on social, working and economic levels. In vivo and clinical findings have enhanced the role of the brain's stress-related system in maintaining SUD behaviors. Several studies have also revealed a high prevalence of post-traumatic symptoms among SUD patients, suggesting that a trauma-informed treatment approach could lead to better treatment outcomes. However, only few studies have evaluated the use of eye move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…To date, preliminary evidence exists suggesting EMDR therapy is efficacious in SUD patients, thanks to previous studies done in that population ( 20 , 63 ). In a more recent publication ( 21 ), a quasi-experimental study of 40 SUD outpatients found that EMDR as an add-on treatment had a pronounced effect in reducing post-traumatic and dissociative symptoms and also caused a significant improvement in the global severity of psychiatric symptoms. The aim of our trial is to provide further evidence of a positive effect of EMDR in this difficult-to-treat population in a larger RCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, preliminary evidence exists suggesting EMDR therapy is efficacious in SUD patients, thanks to previous studies done in that population ( 20 , 63 ). In a more recent publication ( 21 ), a quasi-experimental study of 40 SUD outpatients found that EMDR as an add-on treatment had a pronounced effect in reducing post-traumatic and dissociative symptoms and also caused a significant improvement in the global severity of psychiatric symptoms. The aim of our trial is to provide further evidence of a positive effect of EMDR in this difficult-to-treat population in a larger RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Until nowadays, there are three published trials in SUD and EMDR: two small randomized controlled trials (RCT) and one non-randomized controlled trial of EMDR vs. treatment as usual (TAU) in patients with SUD ( 19 21 ). They have suggested that EMDR, compared to the control group, significantly improves craving ( 19 ), depression, anxiety, self-esteem ( 19 , 20 ), and dissociative symptoms ( 21 ), but results must be repeated with larger samples. A large scale RCT is currently underway ( 22 ) to determine the efficacy of EMDR in reducing PTSD symptoms in an inpatient sample with comorbid SUD and PTSD or sub-threshold PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…While studies using EMDR therapy to treat SUDs have theoretically informed clinical practice, 41 - 52 a gap in research exists supporting its efficacy, considering that there have only been 3 randomized controlled trials (RCTs). 53 - 55 Nonetheless, the promising prospect of using EMDR therapy to treat SUDs has generated 4 different addiction-specific EMDR therapy protocols: the desensitization of triggers and urge reprocessing (DeTUR) protocol, 56 , 57 (an urge reduction protocol that targets the triggers that bring up uncomfortable feelings leading to urges), the craving extinguished (CravEx) approach, 58 (focuses on the reprocessing of the addiction memory leading to stabilization in the addiction), an approach on dysfunctional positive affect, 59 (targets the dysfunctional positive affect associated with a behavior or person that can block access to a traumatic memory), and the feeling-state addiction protocol (FSAP 60 ) (a modified form of EMDR therapy that breaks the fixation of a positive feeling event associated with an addictive behavior).…”
Section: Emdr Therapy To Treat Sudsmentioning
confidence: 99%
“…A quasi experimental study 43 assessed the effectiveness of combined standard EMDR therapy and AF-EMDR therapy in treating posttraumatic and stress-related symptoms in 40 patients with SUDs. This study implemented the standard EMDR therapy protocol and AF-EMDR therapy protocols (CravEx, 58 an approach on dysfunctional positive affect, 59 FSAP, 60 and DeTUR 56 , 57 ) in accordance with the PEIA.…”
Section: Combined Standard and Af-emdr Therapymentioning
confidence: 99%
“…EMDR therapy facilitates the accessing and processing of traumatic memories and other adverse life experience to bring these to an adaptive resolution. [12] conducted a study to assess the benefits of a combined trauma-focused (TF) and addiction-focused (AF) EMDR intervention among 40 patients with PTSD/SUD. Of the 40 patients, 20 received treatment as usual (TAU), which consisted of individual and group counseling and psychoeducation on SUD; the other 20 patients were treated with TAU plus EMDR.…”
Section: Ptsd/sud Treatmentmentioning
confidence: 99%